Pengetahuan Wisatawan Mancanegara atas Kehadiran Patung Garuda Wisnu Kencana sebagai Ikon Pariwisata Indonesia - Supina Supina (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
In 2018, Indonesia has a new tourism icon, namely Garuda Wisnu Kencana Statue, which located in Bali, the most famous tourist destination in Indonesia. The presence of this tourism icon is certainly expected to support increasing numbers of tourists to Bali and Indonesia, especially for foreign tourists. One year has passed but there still no tourism improvement from the presence of this tourism icon, there are no major activities that can invite tourists to visit and there is no research on this tourism icon. Therefore, descriptive research was conducted by distributing questionnaires through online media to foreign tourists from five continents in the world to find out whether foreign tourists knew about the presence of the Indonesian tourism icon Garuda Wisnu Kencana Statue. The results of this study show that 87.5% of respondents from 28 countries in various parts of the world did not know about the presence of this new tourism icon, and of course, there was no significant impact resulting from the tourism icon. The low level of knowledge of the presence of tourism icons surely related to the marketing method both carried out by the local tourism government and the central tourism government. Discussion of marketing methods certainly requires further complete research but the results of questionnaires show that according to respondents one of the best marketing media to promote a new tourism icon is social media and the internet/website.